NILAI-NILAI PENDIDIKAN AGAMA ISLAM DAN KEBANGSAAN DALAM SYAIR YALAL WATHON - Muhammad Izzuddin; Khoirotul Idawati (Fakultas Tarbiyah Institut Agama Islam Bani Fattah Jombang, 2023)
This study aims to provide an explanation of the values of Islamic religious education and national education contained in a series of verses or poems of Yalal Wathon written by KH. Abdul Wahab Hasbullah (later written by researchers with Kiai Wahab). The writing of poems composed by Kiai Wahab is one form of effort and effort he made in providing education as well as building awareness of the nation's citizens in loving the homeland (hubb al-Wathon), defending the state and nation, and adding the soul (rûh) patriotime and nationalism in them. The type of research used is library research using documentation methods that are used as data sources. In analyzing the data that has been obtained, the techniques used are content analysis and also descriptive analysis. The findings and research found and studied by researchers there are at least three clusters of Islamic religious education values, namely: (1) creed, (2) shari'ah, and (3) morals. While the values of national education found by researchers in the poem Yalal Wathon consist of empath al, namely: (1) unity and unity of the nation, (2) love of the motherland, or hubb al-Wathon (3) defending the country and homeland, (4) building national unity.